Investigation of Boundary Effects on the Natural Cavitating Flow around a 2D Wedge in Shallow Water - Xin Chen; Ying Chen; Jia-Yi Cao; Jie Li (Modelling and Simulation in Engineering)
When a cavitated body moves in shallow water, both flexible free surface and rigid bottom wall will produce great influence on the cavity pattern and hydrodynamics to change the motion attitude and stability of the body. In this paper, a single-fluid multiphase flow method coupled with a natural cavitation model was employed to study the effects of two kinds of boundaries on the natural cavitating flow around a two-dimensional symmetry wedge in shallow water. Within the range of the cavitation number for computation (0.05 ~ 2.04), the cavity pattern would be divided into three types, namely, stable type, transition type and wake-vortex type. The shape of the free surface is fairly similar to that of the cavity's upper surface with well right-and-left symmetry. However, when the immersion depth and the cavitation number are decreasing, the symmetry of the cavity shape is destroyed due to the influence of bottom wall effects. When the cavitation number is less than about 0.1, with the immersion depth going down, free surface effects exerts a stronger influence on the drag coefficient of this 2D wedge, whereas wall effects bring a stronger influence on the lift coefficient.